Sagot :
Answer:
A.
Step-by-step explanation:
Hope it'll help
#CarryOnLearning
STANDARD FORM
Directions: Rewrite (x+2)(x+2)=0 in standard form
[tex]A.\:x^{2} +4=0[/tex]
[tex]{\boxed{B.\:x^{2} +4x+4=0}}[/tex]
[tex]C.\:x^{2} +2x+4=0[/tex]
[tex]D.\:(x+2)=0[/tex]
Answer:
[tex]{\purple{\boxed{\purple{\huge{\boxed{\sf{x^{2} +4x+4=0}}}}}}}[/tex]
Solution:
[tex]{\tt{axx^{2} +bx+c=0}}\\{\tt{(x+2)(x+2)=0}}\\{\tt{x(x)+x(2)+2x+2(2)=0}}\\{\tt{x^{2} +2x+2x+4}}\\{\boxed{\tt{x^{2} +4x+4=0}}}[/tex]
[tex]{\blue{\boxed{ItzyMidzy:))}}}[/tex]
#CarryOnLearning